Differential coupling of visual cortex with default or frontal-parietal network based on goals - Chadick, James Z; Gazzaley, Adam (Nature neuroscience, 2011)
This study uses fMRI to find that visual cortical areas involved in processing task-relevant information are functionally connected with the frontal-parietal network, but those processing task-irrelevant information are simultaneously coupled with the default network. The strength of visual cortex/default network functional connectivity was predictive of subjects' abilities to suppress irrelevant information. The relationship between top-down enhancement and suppression of sensory cortical activity and large-scale neural networks remains unclear. Functional connectivity analysis of human functional magnetic resonance imaging data revealed that visual cortical areas that selectively process relevant information are functionally connected with the frontal-parietal network, whereas those that process irrelevant information are simultaneously coupled with the default network. This indicates that sensory cortical regions are differentially and dynamically coupled with distinct networks on the basis of task goals.